Specific changes of erythroid regulators and hepcidin in patients infected by SARS-COV-2. (15th March 2022) - Delaye, Jean-Baptiste; Alarcan, Hugo; Vallet, Nicolas; Veyrat-Durebex, Charlotte; Bernard, Louis; Hérault, Olivier; Ropert, Martine; Marlet, Julien; Gyan, Emmanuel; Andres, Christian; Blasco, Hélène; Piver, Eric
Abstract : Iron metabolism is tightly linked to infectious and inflammatory signals through hepcidin synthesis. To date, iron homeostasis during SARS-CoV-2 infection has not yet been described. The aim of this study is to characterize the hepcidin and erythroid regulators (growth differentiation factor 15 (GDF-15) and erythroferrone (ERFE)) by measuring concentrations in plasma in context of COVID-19 disease. We performed a single-center observational study of patients with COVID-19 to evaluate concentrations of main regulatory proteins involved in iron homeostasis, namely: hepcidin, ERFE and GDF-15. SARS-CoV-2 infection (COVID-19 + ) was defined by a positive RT-PCR. Sixteen patients with COVID-19 + were gender-matched and age-matched to 16 patients with a sepsis unrelated to SARS-CoV-2 (COVID-19 − ) and were compared with non-parametric statistic test. Clinical and hematological parameters, plasma iron, transferrin, transferrin saturation, ferritin, soluble transferrin receptor and C reactive protein were not statistically different between both groups. Median plasma hepcidin concentrations were higher in the COVID-19 + group (44.1 (IQR 16.55–70.48) vs 14.2 (IQR 5.95–18.98) nmol/L, p=0.003), while median ERFE and GDF-15 concentrations were lower in the COVID-19 + group (0.16 (IQR 0.01–0.73) vs 0.89 (IQR 0.19–3.82) ng/mL, p=0.035; 2003 (IQR 1355–2447) vs 4713 (IQR 2082–7774) pg/mL, p=0015), respectively) compared with the COVID-19 − group. This is the first study reporting lower ERFE and GDF-15 median concentrations in patients with COVID-19 + compared with patients with COVID-19 −, associated with an increased median concentration of hepcidin in the COVID-19 + group compared with COVID19 − group.